The party school education and corporate innovation: Evidence from SOEs in China - Beladi, Hamid; Hou, Qingsong; Hu, May (Journal of Corporate Finance, 2022)
This paper examines the impact of early Party school education for top executives on corporate innovation using Chinese listed SOEs data during 2003–2017. We find that SOEs with top executives who get a Party school degree engage in less innovative activities with the lower number of patent application and grants. The text description of the patents applied by the company is less similar to the text description of the company's main business operation, even filed patents are less capable of improving the future performance if SOEs' executives get a Party school degree. We further find that top executives with the Party school degree affect SOEs' innovation activities mainly through the government intervention originated from covert alumni relationship with local officials, which intensifies the executives' political promotion incentive. Our results are robust after we control for other managerial background characteristics, political connection, R&D expenditure and potential endogeneity. Our paper offers first evidence on the economic consequences of Party school education in China.